Factors Affecting Primary Health Care Services Utilization: A Cross-Sectional Study - Abdulaziz Fahad Abdulaziz Alsharif , Naif Hamood Qussairy , Ahmed Jebreal Ahmad Quseiry , Ahlam Saleem A Almagnoni , Ruby Abdulrahman Mahmoud baderaldeen , Nami Abbad Abdullah Altowairqi , Fahad Radah Kalaf Althubyani; Abdulghani Jaber Saad Althobaiti , Turki Mastour Althobaiti , Adel Awwadh A Althobaiti , Muneer Moleh Alharbi , Randa Mohsan Aboeid (Migration Letters, 2022)
Background: Primary health care services are the keystone of health care systems because it serves as the first contact between patients and the health care system. Primary health care (PHC) is essential towards achieving universal health coverage. It is also an integral and critical component of the entire health care system of any country. So, these services should be accessible, affordable and available to the entire population, irrespective of their political, financial or social class. Improving PHC services require understanding context-specific factors influencing utilization. The study aims: To assess the factors affecting PHC services utilization in KSA. Methods: A cross-sectional community-based survey was conducted from January to March 2022. Information on socio-demographic characteristics, utilization of PHC services, community and PHC facility-related factors associated with utilization of PHC services was obtained from 335 adult residents aged ≥ 18 years using a pre-tested semi-structured interviewer administered questionnaire. Data were analyzed using descriptive and inferential statistics at 5% level of significance. Results: of the 335 respondents, 155 (46.2%) reported utilization of PHC services the last time they were sick. Of 178 respondents who did not utilize PHC services, 51 (28.7%) reported poor quality health services, 41 (23.0%) unavailability of medical doctors, 31 (17.4%) long patient waiting time and 25 (14.0%) unavailability of drugs as reasons for non-utilization. Being a female (AOR = 2.3 (95% CI 1.3 - 4.0)), affordability of health services (AOR = 2.4 (95% CI 1.3 - 4.6)), inadequacy of healthcare staff (AOR = 0.3 (95% CI 0.1 - 0.5)), shorter hospital waiting time (AOR = 2.2 (95% CI 1.2 - 4.3)) and satisfaction with PHC services during previous visit (AOR = 2.6 (95% CI 1.1 - 6.3)) influenced utilization of PHC services. Conclusion: PHC services utilization was low. Improving utilization would require addressing cost of health services, adequacy of healthcare staff, patient waiting time and ensuring patient satisfaction with PHC services.